Analisis y propuesta de un reglamento de admisión y empleo, de funciones y valuación de puestos para la Empresa Distribuciones Superior de la ciudad de Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos, para el año 2016 - Chamba Dias, Rosibel del Carmen (2017)
This research has as a general objective, to determine mechanisms for a Regulation of Admission and Employment, of Functions and Valuation of Positions, with models of human talent management in the company DISTRIBUCIONES SUPERIOR of the city of Nueva Loja Cantón Lago Agrio: The materials and methods used were: inductive method which allows to carry out the survey of the information through the survey; analytical method through the diagnosis for the interpretation and evaluation of the positions and their classification; this formed a methodological and systematic process. Through direct observation that served to analyze the structure of the company ¨Distribuciones Superior¨ as well as it was possible to gather information about how the personnel is handled and the activities carried out by each worker. A survey was also conducted in order to obtain accurate information for the valuation of positions. The same one that helped us define the number of positions within the company: That there are 17 staff positions that make up "Superior Distributions", among which are: Manager, Secretary, Digitizers, Accountant, Salespeople, Sales Manager, Drivers, Delivery Assistant, Bodeguero and Warehouse Assistant In addition, an interview was conducted with the manager, obtaining personal information about the company he represents, where he announces that "Superior Distributions" does not have a Regulation for Admission and Employment, Functions and Valuation of Positions. The present work concludes as a tool that allows improving the administration of human talent, allocating the spaces and functions so that each worker meets the specific objectives of his position and this leads to the achievement of the goals of the company. The conceptual part consolidates the technical foundations necessary for the preparation of the proposal, the review of issues related to the problems that contribute and consolidate an adequate scientific base. While the results are recorded the diagnosis of the company 'Higher Distributions' to be able to determine the shortcomings that exist and subsequently, with the valuation of positions it was possible to determine the levels and the categories in which each one of them must be. The discussion of results, is made up of the information collected from which follows the following: Finally, it is recommended to Top Distrubutions the application of this manual that improves the control and management of the human talent of the company, with principles of efficiency and effectiveness in each of the functions and positions assigned..